A Seismic Retrofit Cost Database for Buildings with a Framed Structure. Issue 2 (May 2014) - Jafarzadeh, Reza; Ingham, Jason M.; Wilkinson, Suzanne
A comprehensive database for the specific challenge of cost prediction when undertaking seismic retrofitting of existing buildings is presented. A rigorous data collection effort performed in Iran resulted in the generation of a database of 158 data points, each pertaining to a public school building with a framed structure. The generated database includes the information on the seismic retrofit cost values reflected in construction tender documents, together with the information on 14 variables envisaged to have a degree of influence on this cost. This information for a given building was carefully elicited from the final enacted documents developed through the seismic retrofit study of that particular school. Construction costs include structural costs and the costs of architecture and finishes. The database could be of value to those attempting to determine key variables that influence retrofit cost, or to those comparing retrofit practices and costs in different areas of the world.